REPRESENTATION OF OPTIMISM IN THE SONG “MATAHA” BY OTHMAN ALIBRAHIM: A THREE-LEVEL SEMIOTIC ANALYSIS BY JOHN FISKE - Azizah Nurmi'raj Amin; Maulidatun Rahmi; Zulkhairi; Chairunnisa Ahsana Amalan Shaliha; Anshar Zulhelmi (El-Tsaqafah : Jurnal Jurusan PBA, 2026)
This research entitled Optimism in Mataha by Othman Alibrahim is a study that examines the meaning of optimism in Mataha popularized by Othman Alibrahim. A musical work for the younger generation, with special attention to the relevance for young people in the Quarter Life Crisis. Data source are taken from song lyrics and video clips of Mataha songs on Youtube Othman Alibrahim. The theory used is John Fiske’s semiotic theory. Researchers analyzed optimism codes using a qualitative descriptive method by collecting data with documentary techniques, listening, and collecting data. The result of this research are to find the Optimism code contained in the song Mataha such as wearing a tight blue super hero costume, gestures standing upright with one hand raised, eyebrows slightly fused and a grinning mouth, jumping gestures, lowering the flag with a ghost image and raising the red flag, as well as taking the camera with wide shot, long shot and medium shot techniques, etc that leads to positive thinking and moving forward to face all challenges